Identification and Utilization of Medicinal Plants in West Wangurer Village, Madidir District, Bitung City, North Sulawesi - Enjel Larega; Meity Neltje Tanor; Helen Joan Lawalata; Orbanus Naharia; Danny Christian Posumah (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
In Indonesia, around 9,600 plant species contain compounds or active ingredients with medicinal properties that people can use for traditional medicine because they are natural compared to modern medicine. Medicinal plants are found in many habitats, however, due to developments in the times, people are increasingly using modern medicine, so it is feared that the introduction of medicinal plants will become extinct. This research aims to identify medicinal plants in West Wangurer Village, Bitung City, and how to use them. The research was conducted in March-April 2023 using an exploratory descriptive method with a qualitative approach. Medicinal plant sampling used a purposive sampling method and data on the use of medicinal plants was obtained from interviews with the community. The research results obtained 30 species of medicinal plants used by the community as medicinal ingredients in West Wangurer Village, Madidir District, Bitung City, North Sulawesi. This medicinal plant is used for various diseases such as fever, hypertension, diabetes, diarrhea, digestive disorders, and others.